Hrubieszów House with a Climate: Resilient Living Environments Inspired by Genius Loci, Tradition and Nature as a Local Response to Global Challenges (EAAE Annual Conference Proceedings, 2025)
Renowned architect and educator Professor Wiktor Zin (1925–2007) promoted heritage and landscape preservation through his TV series With a Pen and Charcoal and by inspiring lectures that often referenced his hometown, Hrubieszów. His legacy inspired the project Local Development of Hrubieszów – from Participation to Implementation, which included the Hrubieszów Climate House (Hrubieszowski Dom z Klimatem) section, led by the CUT Faculty of Architecture. The project documented disappearing traditional wooden houses and gardens to strengthen cultural identity, promote heritage preservation, and develop climate-resilient, tradition-based housing. Using a research-by-design approach with fieldwork and surveys, it applied transhistorical pedagogy and bionic design to creatively address present-day challenges.One of the key goals was to introduce students to Professor Zin’s vision of architecture – rooted in the native landscape – seen as a harmony of beauty, function and care. He believed buildings evolved from life and not just design, and praised wooden houses and gardens for their organic vitality. Field research, including at Zin’s family home – an archetype of a Hrubieszów homestead – deepened this understanding. The outcome was a set of projects dubbed 10+1 Hrubieszów Climate Houses and Gardens (10+1 Hrubieszowskich Domów i Ogrodów z Klimatem), created by students and academic teachers. These projects reinterpret local traditions using low-tech, nature-based, and circular design to build resilient, community-driven habitats. Rather than following standardised, design-catalogue – based solutions, they respond to the place and to people – proving that continuing tradition is not nostalgia, but a vital, locally rooted answer to global challenges.Sykta, Izabela, and Anna Staniewska, eds. House and Garden in the Landscape of Hrubieszów. History, Tradition, Spirit of the Place; House and Garden in the Landscape of Hrubieszów. Design in Harmony with Tradition and Climate; Gierbienis, Marcin, and Agnieszka Greniuk, eds. 10+1 Hrubieszów Houses and Gardens with a Climate. Design in the Context of Place and Time. Oficyna Wydawnicza Atut. Wrocławskie Wydawnictwo Oświatowe, Kraków – Hrubieszów, 2024.